Prediction of bubble velocities in air-water two-phase flow using void fraction profiles / Ahmad Najimuddin Ismail - Ahmad Najimuddin, Ismail (2019)
The heat transfer system is the most important application in a power generation plant, particularly in a thermal power plant. With a greater number of pipe bursting accidents happened in thermal power plants due to steam-vapor mixture two-phase flow phenomena, the need for enhancing plant safety level is substantially emerging. Many researchers analyze several parameters such as void fraction, flow rate, temperature and pressure in efforts to improve the plant safety level. Numerous studies on two-phase flow were conducted through simulation, modeling, numerical analysis, theoretical analysis, and comparative study. The present work is basically the investigation and prediction of bubble velocities using the void fraction profiles in air-water two-phase flow via experimental works. The experiment was conducted in an industrial scale vertical two-phase flow rig which consists of a 6.2-m length of transparent pipe with an inner diameter of 20-mm and implanted void sensor on the inner wall. Five different combinations of gas and liquid superficial velocities are designed and used in this experiment. Other variables namely temperature, pressure, pipe diameter and length were kept as constant to simplify the analysis. Experimental results confirmed that bubble velocities can be predicted using the void fraction profiles. Highest void fraction value of 0.40 and the transition of bubbly flow to slug flow occurred easily at high gas superficial velocity at constant low liquid superficial velocity. However, at a higher liquid superficial velocity, the bubbles became unsteady and distorted easily resulting of transition from slug flow to churn flow which is chaotic and unstable. The bubble velocity increased when gas superficial velocity was below 0.05 m/s and void fraction value more than 0.3.